2020
DOI: 10.1002/app.48950
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property relationship of poly(cyclohexane 1,4‐dimethylene terephthalate) modified with high trans‐1,4‐cyclohexanedimethanol and 2,6‐naphthalene dicarboxylicacid

Abstract: A series of novel poly(1,4-cyclohexanedimthylene terephthalate-co-1,4-cyclohxylenedimethylene 2,6-naphthalenedicarboxylate) (PCTN) copolyesters were successfully melt polymerized using different content of trans-or cis-isomers. Before evaluations, the performance properties, their actual chemical composition, chemical structure, and molecular weight were determined using proton nuclear magnetic resonance ( 1 H-NMR), Fourier transform infrared spectroscopy (FTIR), and intrinsic viscosity (IV) measurements. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…TPA‐ 30/70cis / trans CHDM polymer (PCT) and TPA‐EG polymer (PET) have T g of 88 and 80 °C and T m of 300 and 260 °C, respectively. [31] Table 2 shows the effect of the major diol and minor diol composition on thermal and mechanical properties.…”
Section: Impact Of Monomer Composition On Properties Of the Copolyestersmentioning
confidence: 99%
“…TPA‐ 30/70cis / trans CHDM polymer (PCT) and TPA‐EG polymer (PET) have T g of 88 and 80 °C and T m of 300 and 260 °C, respectively. [31] Table 2 shows the effect of the major diol and minor diol composition on thermal and mechanical properties.…”
Section: Impact Of Monomer Composition On Properties Of the Copolyestersmentioning
confidence: 99%
“…PCITN copolyester was melt polymerized using two different 5 L batch reactors of the pilot-scale melt polymerization reactor [ 22 ]. For esterification, the residual oxygen was removed from the reactor by purging pure nitrogen (N 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The PCTN copolyester was synthesized using our previously reported method 17 . The pellets of PCTN copolyester with chemical composition of CHDM as a diol component and the mixture of TPA and NDA as a dicarboxylic acid component in a ratio of 40: 60 mole % of TPA: NDA, were melt polymerized using a piolet scale melt polymerization reactor.…”
Section: Methodsmentioning
confidence: 99%
“…But a higher amount of second diacids results in high cost and processing issues 14–16 . In our previous research, 17 we reported the successful synthesis of novel poly(1,4‐cyclohexanedimthylene terephthalate‐co‐1,4‐cyclohxylenedimethylene 2,6‐naphthalenedicarboxylate) (PCTN) copolyesters by two‐step melt polymerization and analyze their performance properties.…”
Section: Introductionmentioning
confidence: 99%